Frequency of nodal metastasis in differentiated thyroid carcinoma - M. Abdullah Al Mamun; Muhammad Ariful Islam; M. Hasibur Rahman; M. Saiful Islam; Mahmud Asif Rifat (International Journal of Research in Medical Sciences, 2023)
Background: Thyroid cancer is the most common endocrine malignancy. Moreover, within thyroid cancer, differentiated thyroid carcinoma (DTC) is the most common variety, with the incidence rising over the past decade. Often, most of the cases present with multicentric disease and presenting with lymph node metastases at the time of diagnosis. Nodal metastasis has prognostic importance, and it may guide surgeons regarding further management. Considering this scientific fact, the study was performed to see the frequency of lymph node metastasis in DTC among the patients admitted to a tertiary care hospital. Methods: This cross-sectional study was conducted in the department of otolaryngology and head-neck surgery, Sher-E-Bangla Medical College Hospital, for 9 months after the acceptance of the protocol. A total of 50 patients (in all age groups) who attended the relevant department due to thyroid malignancies were approached and interviewed. Thorough history taking, physical examination, and relevant investigation were done and recorded into separate case record forms. Informed written consent was taken from each subject. Following collection, data were coded and inputted into statistical software. Data analysis was done with SPSS 21 according to the objective of the study. Data were presented in the form of tables, and charts. Results: Among the 50 patients, the mean age of the patients was 47.86±15.69 SD (years) with minimum and maximum ages of 14 and 78 years respectively. The male-female ratio was 1:4 (20% male vs 80% female). Papillary carcinoma was the most frequent (88%) followed by follicular (10%). Nodal metastasis was most common in the papillary variety, about 54.55% of cases, whereas 20% were present in the follicular variety. The majority of the patients underwent total thyroidectomy with neck dissection (90%) and the remaining cases were managed by lobectomy (10%). Conclusions: This study concluded that nodal metastasis was present in 54.55% of cases of papillary carcinoma.